고장력강(HT50) 레이저용접부의 용접잔류응력 및 파괴인성 특성 - 노찬승; 방희선; 방한서; 오종인; Ro, Chan-Seung; Bang, Hee-Seon; Bang, Han-Sur; Oh, Chong-In (Han-guk haeyang gonghak hoeji (Online), 2007)
Recently, many industries have been employing the application of laser beam welding, due to the resulting high welding quality, such as smaller width of melting and heat affective zone, smaller welding deformation, and fine grains of weldment, compared to arc welding. However, in order to appropriately utilize this welding process with steel structure, the characteristics of welding residual stresses and fracture toughness in welded joints are to be investigated for reliability. Therefore, in this study, the mechanical properties of weldments by arc and laser welding are investigated using FEM to confirm the weldability of laser welding to the general structural steel (HT50). The Charpy impact test and 3-points bending CTOD test are carried out in the range of temperatures between $-60^{°}C\;and\;20^{°}C$, in order to understand the effect on the fracture toughness of weldments. From the research results, it has been found that the maximum residual stress appears at the center of plate thickness, and that the fracture toughness is influenced by strength mis-match.